Three-dimensional anthropometric analysis: Differences between elite Australian rowers and the general population - Schranz, N.; Tomkinson, G.; Olds, T.; Daniell, N. (Journal of Sports Sciences, 2010)
The aim of this study was to quantify the anthropometric differences between elite senior Australian rowers and the Australian adult population using three-dimensional (3D) whole-body scanning. The dimensions of senior rowers competing at the 2007-2008 Australian Rowing Championships were compared with those of an age-matched sample of Australian adults. Mass, height, and sitting height were measured before the participants underwent a 3D whole-body scan, with lengths, breadths, girths, cross-sectional and surface areas, and volumes extracted from each scan. Differences in means and variability between the two groups were expressed as standardized effect sizes and ratios of coefficients of variation. Heavyweight rowers were generally much larger than the general population in absolute size, with 3D dimensions and height and mass showing the largest effects. In contrast, lightweight rowers were generally similar or smaller in absolute and proportional size. The dimensions of rowers, especially the lightweights, were also generally less variable than those of the general population. The greatest differences between elite rowers and the general population were seen in dimensions that could not be captured without 3D scanning, such as segmental volumes and cross-sectional areas.